Implementasi Pembelajaran Bina Pribadi Islami (BPI) pada Peserta Didik dalam Membangun Karakater Religius - Nainggolan, Ahmad; Nurfadhilah, Noviana; Bulan, Devina Dwi (azkiya, 2024)
This study aims to determine how the Implementation of Bina Pribadi Islami (BPI) building religious character of Students at SDIT Asiddiiqi Jambi City. Using a qualitative approach with field research methods. The research subjects involved classes IV and VI totaling 55 students, the Principal, class teachers and parents of students. Using research instruments interviews, observation and documentation. The results of the study explain that the BPI Learning process with the concept of habituation, as well as the importance of the teacher's spirit in the world of education can build students' religious character. There is good cooperation between student parents and the school. The presence of periodic debriefing for teachers, special parenting seminars for parents, and efforts to establish good communication and cooperation between teachers and parents, namely by forming a grub via WhatsApp as a forum for discussion / sharing.